2012
DOI: 10.2169/internalmedicine.51.8294
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of the Bile and Pancreatic Ducts due to Compression by an Unruptured Abdominal Aortic Aneurysm (AAA): A Case Ameliorated by an Endovascular Stent Grafting

Abstract: An 88-year-old woman was referred to our hospital due to abdominal discomfort. Imaging modalities showed an abdominal aortic aneurysm (AAA) compressing the duodenum, the distal common bile duct and the head of the pancreas concurrent with distension of the proximal bile and main pancreatic ducts in the body and tail of the pancreas. After admission, the patient underwent endovascular stent grafting to treat the AAA. The size of the aneurysm decreased and the dilatation of the bile and pancreatic ducts became l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[18,21] Fukui et al reported a case with unspecific abdominal symptoms and compression of the distal common bile duct with distension of the proximal bile and main pancreatic ducts in the body and tail of the pancreas by a growing AAA. [23] The patient was treated successfully by endovascular stent grafting via the femoral artery and recovered completely.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[18,21] Fukui et al reported a case with unspecific abdominal symptoms and compression of the distal common bile duct with distension of the proximal bile and main pancreatic ducts in the body and tail of the pancreas by a growing AAA. [23] The patient was treated successfully by endovascular stent grafting via the femoral artery and recovered completely.…”
Section: Discussionmentioning
confidence: 94%
“…To our best knowledge there are only 12 cases according to literature (see Table 2) reporting aneurysms of the abdominal aorta as the cause for acute obstruction of the pancreatic duct or distal common bile duct. [12][13][14][15][16][17][18][19][20][21][22][23] Also among radiological findings of uncommon types and causes of pancreatitis, aneurysms of the abdominal arteries, especially AAA, remain a rarity. [8] According to the widely used Atlanta classification, our patient suffered from acute severe pancreatitis by presenting pulmonary insufficiency, hypotension and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EVAR has been demonstrated as an effective tool in relieving abdominal compression symptoms caused by AAA: Fukui et al. 32 reported a case of biliary and pancreatic ducts compression caused by AAA successfully treated by EVAR.…”
Section: Discussionmentioning
confidence: 99%